Graphing and measuring Covid's first wave impact on the Bolivian economy - Gover Barja Daza (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2021)
The Bolivian monthly index of economic activity along with ARMA models are used in an attempt to graph and measure the impact of Covid's pandemic on the Bolivian economy. The accumulated difference between the observed and counterfactual values show an overall 12.6% loss of economic activity in the 10 months from February to November 2020 of the first Covid wave, with a tilted W-shape short-run recovery just before the beginning of the second wave in December 2020. Break[1]down into the twelve Bolivian economic sectors show wide heterogeneity in depth of impact and speeds of recovery during the same period.
Keywords: C22; O54; E32; E37; Y10; 330; Covid-19; Interrupted time series analysis; ARMA-GARCH models; Bolivia; Coronavirus; Wirkungsanalyse; ARCH-Modell; Zeitreihenanalyse; Bolivien